Computer-controlled closed-loop norepinephrine infusion system for automated control of mean arterial pressure in dogs under isoflurane-induced hypotension: a feasibility study - Sasaki, Kazumasu; Kawada, Toru; Matsushita, Hiroki; Yokota, Shohei; Kakuuchi, Midori; Yokoi, Aimi; Yoshida, Yuki; Morita, Hidetaka; Sato, Kei; Nishikawa, Takuya; Kutter, Annette P. N.; Kataoka, Yasuyuki; et al. (Frontiers in Veterinary Science, 2024)
Intra-operative hypotension is a common complication of surgery under general anesthesia in dogs and humans. Computer-controlled closed-loop infusion systems of norepinephrine (NE) have been developed and clinically applied for automated optimization of arterial pressure (AP) and prevention of intra-operative hypotension in humans. This study aimed to develop a simple computer-controlled closed-loop infusion system of NE for the automated control of the mean arterial pressure (MAP) in dogs with isoflurane-induced hypotension and to validate the control of MAP by the developed system. NE was administered via the cephalic vein, whereas MAP was measured invasively by placing a catheter in the dorsal pedal artery. The proportional-integral-derivative (PID) controller in the negative feedback loop of the developed system titrated the infusion rate of NE to maintain the MAP at the target value of 60 mmHg. The performance of the developed system was evaluated in six laboratory Beagle dogs under general anesthesia with isoflurane. In the six dogs, when the concentration [median (interquartile range)] of inhaled isoflurane was increased from 1.5 (1.5-1.5)% to 4 (4-4)% without activating the system, the MAP was lowered from 95 (91-99) to 41 (37-42) mmHg. In contrast, when the concentration was increased from 1.5 (1.0-1.5)% to 4 (4-4.8)% for a 30-min period and the system was simultaneously activated, the MAP was temporarily lowered from 92 (89-95) to 47 (43-49) mmHg but recovered to 58 (57-58) mmHg owing to the system-controlled infusion of NE. If the acceptable target range for MAP was defined as target MAP ± 5 mmHg (55 ≤ MAP ≤ 65 mmHg), the percentage of time wherein the MAP was maintained within the acceptable range was 96 (89-100)% in the six dogs during the second half of the 30-min period (from 15 to 30 min after system activation). The median performance error, median absolute performance error, wobble, and divergence were -2.9 (-4.7 to 1.9)%, 2.9 (2.0-4.7)%, 1.3 (0.8-1.8)%, and -0.24 (-0.34 to -0.11)%•min -1 , respectively. This system was able to titrate the NE infusion rates in an accurate and stable manner to maintain the MAP within the predetermined target range in dogs with isoflurane-induced hypotension.